(untitled) (World Science, 2019)
The work, presented below, describes the findings of the study of emergence and gradual increase of manifestations of violation of the morphometric indices of the articular cartilage in the distal epiphysis of the femur and proximal epiphyses of the tibia at different terms of experimental opioid exposure (in norm, at the end of the 1st, 2nd, 3rd, 4th, 5th, and 6th weeks and after a two-week withdrawal at the end of the 8th week. The goal was achieved using the morphometric method of measuring the layers of the articular cartiliage of the distal epiphysis of the femur and proximal epiphyses of the tibia in histological preparations obtained at different terms of experimental opioid exposure. Histologic preparations were obtained by applying a generally accepted method. The results of this research will form pathomorphometric basis, which can be applied for a comparative analysis of the dynamics of emergence, development and gradual increase of change in morphometric indices of structural components of the articular cartilage at early stages.